Analisis Uji Beda Sebelum Dan Sesudah Reverse Stock Split Terhadap Abnormal Return Dan Likuiditas Perdagangan Saham - Citra Nurul Hidayati; Ronny Malavia Mardani; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research aims to analyze differences abnormal returns and stock trading liquidity between before and after reverse stock split in 2014-2019 on the Bursa Efek Indonesia. This research uses descriptive statistical analysis methods. This type of research is historical research using the event study approach method. The observation period of the research will last for 11 days, which includes 5 days before reverse stock split and 5 days after reverse stock split. The population in this research are companies listed on the IDX 2014-2019 with a sample of 7 companies. The results of the research using Paired Sample T-test showed that there were no differences in results between abnormal return and stock trading liquidity before reverse stock and after reverse stock split. This happens because the reverse stock split is considered not to contain signals and information that cam trigger a reaction on the capital market, so that there is difference in conditions between before and after reverse stock. Keywords: Abnormal Return, Stock Trading Liquidity, Reverse Stock Split.